Case report: Long-term progression-free survival in advanced ovarian cancer treated with apatinib in first-line maintenance treatment - Zan, Ning; Zhang, Xuan; Yu, Danfei; Liu, Juan; Lin, Zhiyu; Zhu, Yanlin (Frontiers in Oncology, 2024)
Ovarian cancer is one of the most common gynecological malignancies. The current first-line treatment strategies for advanced ovarian cancer include surgery, chemotherapy, and maintenance therapy. Bevacizumab and poly (ADP-ribose) polymerase inhibitors (PARPi) are primary maintenance treatments for advanced ovarian cancer. Previously, many patients declined these therapies before medicare coverage because of high costs. Bevacizumab and apatinib are anti-tumor angiogenic agents. In this case study, we describe a patient with advanced ovarian cancer who underwent neoadjuvant chemotherapy, interval debulking surgery, and adjuvant chemotherapy. She declined bevacizumab and PARPi maintenance therapy owing to the prohibitive expenses. The patient was administered off-label apatinib and achieved a progression-free survival of 54 months. Thus, apatinib may offer substantial therapeutic value as a first-line maintenance therapy in advanced ovarian cancer.